Padronização da técnica de deslizamento dos dedos em ágar nutriente para estudo da microbiota das mãos - Nascimento, Wellinton Muniz do (2015)
The finger-streak technique is commonly used in qualitative studies to investigate contamination of hands in hospital practice. However, it has not yet been standardized for quantitative studies with regard to transient microbiota on the hands. Current investigation proposes an adaptation of finger-streak technique for its standardization to assess the degree of hand contamination. Test organisms in current study were derived from culture collections and included the following microbial species: Staphylococcus aureus, Enterococcus faecalis, Escherichia coli, Klebsiella pneumoniae, Serratia marcescens, Acinetobacter baumannii, Pseudomonas aeruginosa and Candida albicans. The contamination of fingertips from human volunteers was carried out by the application of 20 µL of a broth culture of test organism and 10-1 to 10-6 dilutions in experiment 1 (comparison techniques) and 10-2 to 10-5 in experiment 2 (correlation techniques). The test organisms were recovered from the fingertips by the finger-streak technique (proposed method) and by glass-bead tube technique (reference method). In experiment 1, the finger-streak technique showed an average confluent growth for contaminant doses of 10 million colony-forming units (CFU) per fingertip (high contamination); semi-confluent with 130,000 CFU per fingertip (medium contamination) and countable colonies of 6,000 CFU per fingertip (low contamination). In experiment 2 there was a correlation between the techniques. Spearman's mean+SD correlation coefficient was 0.81±0.16 for the tested organisms.